Assessment of cartilage loss at the wrist in rheumatoid arthritis using a new MRI scoring system. Issue 11 (14th May 2010) - McQueen, Fiona; Clarke, Andrew; McHaffie, Alex; Reeves, Quentin; Williams, Megan; Robinson, Elizabeth; Dong, Jing; Chand, Arista; Mulders, Desiree; Dalbeth, Nicola
Abstract : Objectives: To develop and test an MRI cartilage scoring system for use at the wrist in rheumatoid arthritis (RA). Methods: MRI scans were obtained using a 3T MRI scanner with dedicated wrist coil in 22 early and 16 established RA patients plus 22 controls. Axial and coronal T1-weighted (precontrast and postcontrast) and T2-weighted turbo spin echo sequences were obtained. Eight wrist joints were scored for cartilage narrowing: distal radioulnar, radiolunate, radioscaphoid, triquetrum-hamate, capitate-lunate, scaphotrapezoid, second metacarpal base-trapezoid and third metacarpal base-capitate, using a system based on the Sharp van der Heijde x-ray joint space narrowing (JSN) score by three radiologists. Fifteen sites at the wrist were also scored for synovitis, bone oedema and erosion using the RA MRI score. Results: Interobserver (three-reader) and intraobserver reliability (readers 1 and 2) for the cartilage score were excellent: intraclass correlations (ICC (95% CI)) 0.91, (0.86 to 0.94), 0.98 (0.96 to 1.00) and 0.94 (0.87 to 1.00), respectively. Cartilage scores (median, range) were higher in the established RA group (11.9, 2.3–27.3) than the early RA group (2.15, 0–6) (p≤0.001) but early RA scores did not differ from healthy controls (2.3, 1–8.7). Cartilage scores correlated with synovitis (R=0.52), bone oedema (R=0.63) and erosion scores (R=0.66), p<0.001 for all, and with x-ray JSN scores (R=0.68 to 0.78). Conclusion: This MRI cartilage score demonstrated excellent reliability when tested in a three-reader system. However, cartilage loss in early RA could not be distinguished from that seen in healthy controls.